THE IMPACT OF SPILLOVER STAGFLATION ON CAPITAL UTILIZATION IN EAST JAVA (IN MACROECONOMIC PERSPECTIVES) 2014-2022 - Anggun Wida Prawira; Syamsul Arifin; Nuryadi (Sekolah tinggi ilmu ekonomi pemuda, 2023)
This study intends to examine the implications of stagflation risk on capital utilization in the East Java from a macroeconomic perspective. Non-random, saturated sampling was used in the sampling procedure. The quantitative nature of this study approach allows for the testing of ideas from unbiased perspectives. Using time series secondary data 2014 to 2022 with capital utilization from the One-Stop Investment and Integrated Services Office (DPMPTSP), inflation and open employment rate from the Bank of Indonesia, and Gross Regional Domestic Product (GRDP) from the Central Statistics Agency (BPS). Data analysis techniques using multiple linear regression processed using ordinary least squares (OLS) by EViews12. The findings were as follows: 1). Capital utilization is positively and significantly impacted by the stagflation trap of gross regional domestic product (GRDP). 2). Capital utilization positive effects from the Stagflation trap of inflation, although the effect is insignificant. 3). The open unemployment rate's Stagflation trap has a positive and significant effect on capital utilization. 4). The macroeconomic stagflation trap, which is represented by the gross regional domestic product (GRDP), inflation rate, and open unemployment rate, has a substantial impact on capital utilization simultaneously. This study's findings are statistically in line with previous findings and theoretical literature.